ETIKA AKADEMIK DAN TANGGUNG JAWAB SOSIAL MEMBANGUN KESADARAN DI KALANGAN MAHASISWA - M.Ridho Efriyanda; Lubis, Sanjai Kurniawan; Oktavia Ramadhani; Demala Sari (CV. Arsy Persada Quality, 2025)
Academic ethics and social responsibility are two essential pillars in higher education that contribute to the character development of students. This study aims to explore students' awareness of academic ethics and social responsibility, as well as how these two aspects can influence each other in everyday life. Through surveys and interviews with students from various disciplines, the research finds that understanding of academic ethics is still low, while awareness of social responsibility tends to be higher. The results indicate that integrating ethical values into the educational curriculum can enhance students' awareness and encourage them to actively participate in society. This research is expected to contribute to the development of better educational policies and encourage educational institutions to instill ethical values and social responsibility in the learning process.